2D/2D V2C mediated porous g-C3N4 heterojunction with the role of monolayer/multilayer MAX/MXene structures for stimulating photocatalytic CO2 reduction to fuels. (November 2022) - Madi, Mohamed; Tahir, Muhammad; Zakaria, Zaki Yamani
Abstract: 2D vanadium carbide (V2 C) MXene nanosheets coupled 2D porous g-C3 N4 (PCN) was designed and tested for photocatalytic CO2 reduction under visible light. Controlled coupling g-C3 N4 with V2 C MXene resulted in higher visible light absorption and efficient charge separation. Comparatively, V2 C MXene found more favorable than V2 AlC MAX due to more proficient charge separation. Highest performance was achieved with optimized 15%-V2 C/g-C3 N4, in which CO and CH4 generation rates of 151 and 205 µmol g −1, respectively, were attained. This enhancement was significantly higher than using V2 AlC/g-C3 N4 and pure g-C3 N4 samples due to higher conductivity and large CO2 adsorption capacity. The performance of V2 C/g-C3 N4 composite was further examined under a variety of conditions such as pressure, catalyst loading, and reducing agents. With increasing pressure, higher yield of CO and CH4 was attained due to increased reactant adhesion to the catalyst surface, whereas increasing catalyst loading has adverse effects. Water was the best reducing agent for CO evolution, while the methanol–water system enhanced CH4 generation. Furthermore, the stability of composite lasted for several cycles without showing any obvious deterioration. The potential outcomes are assigned to a porous structure with intimate contact, effective charge carrier separation and porous 2D g-C3 N4 transporting electrons towards MXene surface. This study shows that 2D V2 C MXene could be a potential carrier for constructing 2D/2D heterojunctions in photocatalytic CO2 reduction to produce useful solar fuel. Graphical Abstract: ga1 Highlights: 2D/2D V2 C/ g-C3 N4 nanosheets heterojunction developed for CO2 reduction to fuels. V2 C MXene is more effective for charge transport and segregation than the V2 AlC MAX. V2 C MXene/g-C3 N4 efficiency was 6.8 times more than g-C3 N4 under solar energy. Reducing agents contributed significantly to the reduction of CO2 to CH4 and CO. Using 2D V2 C with a g-C3 N4 photocatalyst, high cycle stability was achieved.